Gene expression changes in macrophages infected with pathogenic M. tuberculosis and non-pathogenic M. smegmatis and M. bovis BCG - Mpongoshe, Vuyiseka (Stellenbosch : Stellenbosch University, 2014)
Thesis (MScMedSc)--Stellenbosch University, 2014.